LEGISLATIVE CONSOLIDATION OF THE EXERCISE OF THE RIGHT TO ARTIFICIAL REPRODUCTION - Слободська, Ірина Андріївна; Процко, Владислава Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the article is devoted to the analysis of the current state of legislative consolidation of the implementation of the right to artificial reproduction. Research methods: the study was carried out using generally accepted methods of scientific cognition, such as analytical, comparative-legal, semantic-cognitive, systemic, statistical, and others. The basis of the methodology in this study is a systematic approach, with the help of which the legislation of Ukraine and international practice of legal regulation of the use of methods of artificial reproduction were studied. Results: authors of the study concluded that the implementation of the right to artificial reproduction requires the development and adoption of highly specialized regulatory legal acts that would fully regulate all relations associated with the exercise by citizens of their rights to artificial reproduction. The problem of consolidating and protecting the reproductive rights of citizens has recently become especially important for Ukrainian society, in particular in connection with the demographic crisis in our country. It is also important to determine the legal nature of these rights in the civil aspect, as reproductive health and family planning are fundamental human rights. Quite often we face significant problems, most of which are related to ignorance of the basic facts about our reproductive health and the possibility of its preservation. The authors believe that the right to artificial reproduction should be considered as a system of separate personal non-property rights of individuals that ensure their natural existence and aimed at the reproductive function. Despite their close connection with the right to maternity and paternity, it would be appropriate to adopt a single legal act in this area, which would enshrine the concept of artificial reproduction, reproductive rights of the parties, would disclose their content and provide guarantees of implementation based on priority. human and civil rights and freedoms.